2022
DOI: 10.1002/ajmg.a.62986
|View full text |Cite
|
Sign up to set email alerts
|

A homozygous missense variant in the WRN gene segregating in a family with progressive pulmonary failure with recurrent spontaneous pneumothorax and interstitial lung disease

Abstract: Interstitial lung disease (ILD) is a condition affecting the lung parenchyma by inflammation and fibrosis and can be caused by various exposures, connective tissue diseases (CTD), and genetic disorders. In this report, a family with five patients having progressive respiratory failure that begins with coughing in adolescence, followed by dyspnea and recurrent spontaneous pneumothorax, and death in early adulthood is presented. The patients were diagnosed to have ILD through clinical and radiological evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…SFXN4 regulated iron metabolism, mitochondrial respiration, and heme metabolism 22 , and SFXN4 deficiency caused macrocytic anemia and mitochondriopathy 23 . Study on SFXN5 was rare, and the limited studies indicated that SFXN5 gene variation might be correlated with interstitial lung disease 24 . It remains unknown, however, what the roles and mechanisms of SFXNs are in pathogenesis of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…SFXN4 regulated iron metabolism, mitochondrial respiration, and heme metabolism 22 , and SFXN4 deficiency caused macrocytic anemia and mitochondriopathy 23 . Study on SFXN5 was rare, and the limited studies indicated that SFXN5 gene variation might be correlated with interstitial lung disease 24 . It remains unknown, however, what the roles and mechanisms of SFXNs are in pathogenesis of HCC.…”
Section: Introductionmentioning
confidence: 99%